The Influence of Environmental Change on Pharmaceutical Companies -- Analysis of Opportunities for Pharmaceutical Companies, Take Roche Inc., Pfizer, and Merck. as an example - Lai Yingkuan (E3S Web of Conferences, 2023)
The impact of natural environment change on biological pharmaceutical companies has become a growing concern in recent years. In response, re-searchers have employed various models to analyze the relationship between natural environment changes and the financial performance of these companies. This paper will use the Capital Asset Pricing Model (CAPM) and Fama-French Three-Factor Model (FF3F) to estimate the impact of natural environment changes on biological pharmaceutical companies. Using secondary data from past studies, this paper conducts a literature review to analyze the impact of natural environmental changes on these companies, particularly in terms of their risk and return tradeoffs. Results from previous research indicate that both CAPM and FF3F models can be used to measure the risk and return trade-offs in the context of natural environmental changes. The CAPM model has been used to identify factors such as natural disasters and climate change that influence the risk of these companies, while the FF3F model has been used to measure the effect of regulatory changes on their stock prices. Overall, this paper brings together previous insights and findings, aiming to provide a deeper understanding of the impact of natural environment change on biological pharmaceutical companies. It concludes that further research is needed to investigate other factors that can influence the performance of these companies in the face of natural environmental changes.